Antibiofilm effects of bacteriocin PCM7-4 on Listeria monocytogenes - Haotian Ma; JinJu Peng; Yang Li; Ruixue Pan; Yuner Long; Yining Zhao; Yuexia Ding; Yi Ma (PLoS ONE, 2025)
Listeria monocytogenes is a significant zoonotic pathogen capable of forming biofilms on food and other materials, representing a considerable risk to human health and animal husbandry. The use of bacteriocins as potential new antibacterial and antibiofilm reagents has attracted considerable interest. This study aimed to determine the inhibitory effects of bacteriocin PCM7−4 on L. monocytogenes biofilm formation. In this study, bacteriocin PCM7−4 of SICs (1/16 × MIC, 1/8 × MIC) significantly inhibited the formation of L. monocytogenes biofilm. Bacteriocin PCM7−4 of SICs significantly reduced the production of bacterial extracellular polysaccharides, and could decrease the bacterial motility, meanwhile, PCM7−4 significantly reduced the number and viability of bacteria within the biofilm. RT-qPCR results showed that bacteriocin PCM7−4 significantly reduced the expression of flagella, community sensing and virulence factor genes associated with biofilm formation. The results demonstrated the considerable potential of bacteriocin PCM7−4 as a therapeutic agent for the prevention and treatment of L. monocytogenes biofilms.